Maine’s Food-Related Workforce: Characteristics and Challenges - Carter, Valerie (Maine Policy Review, 2011)
As described in this article, people who produce, process, transport, sell, prepare, and serve food are a key part not only of the food system but the economy overall. In Maine, by a conservative estimate they are almost 17 percent of the total workforce and range from farmers and fishermen to truckers, cooks, waitstaff, and cashiers. Some work in food-related enterprises, while others perform food-related tasks in other kinds of organizations, such as schools or hospitals. Although the food-related workforce is diverse, the author points out that the majority of workers and entrepreneurs are poorly paid; many work only part-time; few have health insurance or other benefits; and many work under hazardous conditions. Sidebars in the article discuss sub-groups of this workforce: refugee agriculture (Amy Carrington), migrant workers (Juan Perez-Febles), and the increase in young farmers in Maine (Elizabeth Banwell).
Keywords: Maine; food system workforce; food system wages; Maine farmers; migrant workers; refugee agriculture